The Legality of Brushing Practices in the Viewpoint of Consumer Protection Law and Telematics Law - Swarianata, Vifi; Puluhulawa, Jufryanto; Apripari, Apripari; Kaku, Rismanto; Puluhulawa, Irlan (Jambura Law Review, 2023)
Instant profit-making patterns have been established by the current online purchasing and selling practices. For example, brushing is the activity of internet retailers or merchants fabricating favorable reviews or fraudulent endorsements to boost the reputation of their goods or services. When a customer receives a product or service that falls short of their expectations, brushing can be harmful. This study aims to investigate the legality of online buying and selling in Indonesia, specifically the practice of "brushing," or using fictitious orders, reviews, and buyers.  The methods used are Statute Approach, Case Approach, Conceptual Approach, Analytical Approach, Theoretical Approach.   The findings indicated that, from the standpoint of Indonesian telematics and consumer protection legislation, brushing activities frequently contravene a number of relevant rules and laws. As a result, brushing may be deemed unlawful in Indonesia and subject to penalties based on relevant legislation. In order to prevent brushing activities, it is critical that the government and regulatory agencies bolster law enforcement, protect consumers from brushing practices, and inform consumers of their rights in this regard. Enforcing stringent regulations and ensuring their efficient implementation are crucial for safeguarding consumers and upholding the integrity of Indonesia's online ecosystem.